Tinjauan Kuat Tekan dan Microstructure pada Mortar ECC (Engineered Cementitious Composites) dan CR (Crumb Rubber) -ECC - Simbolon, Eka Silvy Maranatha; Aswin, Muhammad; Syam, Bustami (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The construction industry continues to develop, which of course has a great influence on the environment. One of the reliable products is engineered cementitious composites (ECC). Usually, ECC products produce green products that are environmentally friendly. The cementitious material of ECC always generated from waste materials and by-products. Meanwhile, the amount of cement used can be less than 500 kg/m3. In this study, palm shell ash (ACS) is used as a cementitious material, and crumb rubber is used as a substitute for fiber. Meanwhile, the amount of cement used is less than 265 kg/m3. In addition to green products, ECC also has superior mechanical properties. Based on the results of the compressive test at the age of 3 days for three types of ECC mortar variations (those are AME, EM and TEM), the average compressive strength was obtained in the range of 19.70-42.67 MPa. As for each type of ECC mortar that is varied with crumb rubber (2.5-12.5%), namely for FCR, CRE and TCRE variations, the average compressive strength is obtained between 17.70-37.28 MPa, there has been a decrease in strength. The addition of ACS to a certain percentage can increase the compressive strength of the ECC, where SiO2 can produce Calcium Silicate Hydrate (CSH) which is a strength contributor to the ECC. Meanwhile, crumb rubber can cause a decrease in compressive strength because it is quite compressible. If viewed from the aspect of microstructure (based on the SEM observations on EM and CRE samples only), the results of the scanning electron microscope - energy dispersive x-ray spectroscopy (SEM-EDX) Mapping test on the samples from the compression test on the ECC mortar show that the ECC mortar matrix has tighter pores and fewer microcracks compared to the crumb rubber ECC (CR-ECC) samples. However, ECC mortar is denser than CR-ECC, so the results of the microstructure have strengthened the results of the mechanical properties tests that have been carried out.